Effects of rest interval length on smith machine bench press performance and perceived exertion in trained men - Tibana, R. A.; Vieira, D. C. L.; Tajra, V.; Bottaro, M.; de Salles, B. F.; Willardson, J. M.; Prestes, J. (Perceptual and Motor Skills, 2013)
Summary.—This study compared two different rest intervals (RI) between sets of resistance exercise. Ten resistance-trained men (M age = 24.3, SD = 3.5 yr.; M weight = 80.0 kg, SD = 15.3; M height = 1.75 m, SD = 0.04) performed five sets of Smith machine bench presses at 60% of one repetition maximum, either with 1.5 min. or 3 min. RI between sets. Their repetition performance, total training volume, velocity, fatigue, rating of perceived exertion, and muscular power were measured. All of these measures indicated that performance was significantly better and fatigue was significantly lower in the 3 min. RI as compared with the 1.5 min. RI, except the rating of perceived exertion which did not show a significant difference. A longer RI between sets promotes superior performance for the bench press.